Legacies of temperature fluctuations promote stability in marine biofilm communities - Luca Rindi; Jianyu He; Mara Miculan; Matteo Dell’Acqua; Mario Enrico Pè; Lisandro Benedetti-Cecchi (Nature Communications)
Abstract The increasing frequency and intensity of extreme climate events are driving significant biodiversity shifts across ecosystems. Yet, the extent to which these climate legacies will shape the response of ecosystems to future perturbations remains poorly understood. Here, we tracked taxon and trait dynamics of rocky intertidal biofilm communities under contrasting regimes of warming (fixed vs. fluctuating) and assessed how they influenced stability dimensions in response to temperature extremes. Fixed warming enhanced the resistance of biofilm by promoting the functional redundancy of stress-tolerance traits. In contrast, fluctuating warming boosted recovery rate through the selection of fast-growing taxa at the expense of functional redundancy. This selection intensified a trade-off between stress tolerance and growth further limiting the ability of biofilm to cope with temperature extremes. Anticipating the challenges posed by future extreme events, our findings offer a forward-looking perspective on the stability of microbial communities in the face of ongoing climatic change.